Using artificial intelligence to improve Beninese ESP advanced learners’ communication skills in Institut de Formation et de Recherche en Informatique (IFRI) and Haute Ecole de Commerce et de Management (HECM) in Benin Republic - TEBA, Corneille Sourou (My University, 2024)
This paper explores the use of artificial intelligence (AI) to enhance the communication skills of advanced learners in English for Specific Purposes (ESP). The impact of integrating AI technology on ESP learners’ communication skills is examined. A mixed and quasi-experimental methodology was employed, involving data collection from teachers and learners through classroom observation, interviews, and questionnaires. These were addressed to three (03) ESP teachers and three hundred (300) learners at HECM and IFRI. The experimental process involved an experimental group (EG) that used AI tools for three months, and a control group (CG) that did not. The collected data was analyzed using a one-way ANOVA test in SPSS 26. The results showed a statistical significant improvement in the oral communication skills of ESP learners who used AI tools. This study suggests that integrating AI technology into the curriculum can enhance learners’ communication skills
Keywords: KEYWORDS: Artificial Intelligence; communication skills; ESP; advanced learners